Skin Tumors Rb(eing) Uncovered - COSTA, CLOTILDE; Paramio, Jesus M.; SANTOS, MIRENTXU (Frontiers in Oncology, 2013)
The Rb1 gene was the first bona fide tumor suppressor identified and cloned more than 25 years ago. Since then, a plethora of studies have revealed the functions of pRb and the existence of a sophisticated and strictly regulated pathway that modulates such functional roles. An emerging paradox affecting Rb1 in cancer connects the relatively low number of mutations affecting Rb1 gene in specific human tumors, compared with the widely functional inactivation of pRb in most, if not in all, human cancers. The existence of a retinoblastoma family of proteins pRb, p107 and p130 and their potential unique and overlapping functions as master regulators of cell cycle progression and transcriptional modulation by similar processes, may provide potential clues to explain such conundrum. Here, we will review the development of different genetically engineered mouse models, in particular those affecting stratified epithelia, and how they have offered new avenues to understand the roles of the Rb family members and their targets in the context of tumor development and progression.